TNF-Mediated Homeostatic Synaptic Plasticity: From in vitro to in vivo Models - Heir, Renu; Stellwagen, David (Frontiers in Cellular Neuroscience, 2020)
Since it was first described almost 30 years ago, homeostatic synaptic plasticity (HSP) has been hypothesized to play a key role in maintaining neuronal circuit function in both developing and adult animals. While well characterized in vitro, determining the in vivo roles of this form of plasticity remains challenging. Since the discovery that the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) mediates some forms of HSP, it has been possible to probe some of the in vivo contribution of TNF-mediated HSP. Work from our lab and others has found roles for TNF-HSP in a variety of functions, including the developmental plasticity of sensory systems, models of drug addiction, and the response to psychiatric drugs.